Kajian Signifikansi Faktor Yang Mempengaruhi Penggunaan e-Learning Pada Siswa SMK Global Informatika Tangerang - Forkas Tiroy Santos Butarbutar; Yuli Haryanto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
Increasing the role of information systems / information technology through e-Learning media allows evaluated so as to know the needs that need to be developed and maintained its existence. For that, there needs to be a study to find out how much e-learning earmarking role in the learning process students in school. The research was done by using Unified Theory of Acceptance and Use of Technology (UTAUT) model that able to explain and predict the factors that significantly influence in the use of e-Learning at SMK Global Informatika Tangerang. The UTAUT model in this study was tested by validation process on the factors that significantly influence in the use of e-Learning done by using SEM analysis and AMOS software. The result of this research is that Effort Expectancy and Facilitating Condition have significant effect on Behavior Intention and Use Behavior. Thus the conclusion obtained is the e-Learning media accessed by students of SMK Global Informatika Tangerang is very easy to understand coupled with the availability of facilities that contribute to the progress of student learning.